ANALISIS PERAN ACCOUNTING THE SAHID RICH JOGJA HOTEL DALAM UPAYA PEMENUHAN BARANG-BARANG KEBUTUHAN TAMU HOTEL - , WAHYUNIS AGUNG RIWAYATI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
A tourism industry especially in the field of hospitality will definitely try to do the best to support the achievement guest satisfaction by fulfilling the needs of guests stuff. In this case the Accounting Department is one part that plays an important role in addressing the needs of the guests. Therefore the need for analysis of the role of Accounting Department in fulfilling guest needs stuff. The purpose of this analysis was to determine the role and process of the fulfillment of goods for guests at The Hotel Sahid Rich Jogja. Subject of this analysis are the parts that are directly involved in the effort to fulfill the needs of guests stuff. The parts that are directly involved in it are Purchasing, Receiving, Cost Control, Store Keeper, Accounts Payable, and General Cashier. Method of data collection is documentation, observation, and interviews. Once all the data is collected it will then be analyzed and created a chart that describes the process of fulfillment of goods for the guests. Through the chart would show how the role of Accounting department in fulfilling the needs of guests stuff. Results of this analysis indicate that the role of the Accounting Department in the fulfillment of goods for hotel guests already established and well-executed, and has been supported by the use of information technology. Additionally outline the procedures that have been applied does not stray far from the theoretical and went pretty smoothly, so that the operational Rich Jogja Hotel Sahid undisturbed.